2020
DOI: 10.1016/j.jtho.2019.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Eighth Edition TNM Lung Cancer Staging System

Abstract: Introduction: We performed a validation study at our institution, the International Union Against Cancer (Union for International Cancer Control latest version of TNM Classification of Malignant Tumors Eighth Edition).Methods: Data were collected from the Queensland Oncology Online registry of NSCLC or SCLC cases between 2000 and 2015 and validated against the Queensland Integrated Lung Cancer Outcomes Project registry using case identification number, first name, last name, and date of birth. Where data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…We reviewed the SEER database ( Myers and Ries, 1989 ) for cases with definite 7th edition AJCC pathological stages between 2010 and 2015, and found that even in patients with T1 stage, 54.2% (4,907/9,049) had lymph node metastasis, while the proportion of lymph node metastasis did not increase significantly with the increase of T stage [T2: 49.9% (5,382/10,793), T3: 65.2% (6,245/9,582), T4: 73.1% (8,991/12,296)]. Clarification of lymph node metastasis status is crucial for the treatment of patients as well as for the assessment of their prognosis ( Hwang et al, 2020 ). The commonly used noninvasive clinical examinations are CT and PET/CT, but these two modalities are not accurate enough for the diagnosis of lymph node metastasis and there is a certain possibility of missing the diagnosis ( Li et al, 2013 ; El-Sherief et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the SEER database ( Myers and Ries, 1989 ) for cases with definite 7th edition AJCC pathological stages between 2010 and 2015, and found that even in patients with T1 stage, 54.2% (4,907/9,049) had lymph node metastasis, while the proportion of lymph node metastasis did not increase significantly with the increase of T stage [T2: 49.9% (5,382/10,793), T3: 65.2% (6,245/9,582), T4: 73.1% (8,991/12,296)]. Clarification of lymph node metastasis status is crucial for the treatment of patients as well as for the assessment of their prognosis ( Hwang et al, 2020 ). The commonly used noninvasive clinical examinations are CT and PET/CT, but these two modalities are not accurate enough for the diagnosis of lymph node metastasis and there is a certain possibility of missing the diagnosis ( Li et al, 2013 ; El-Sherief et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggested that low CHRDL1 in LUAD was significantly related to advanced clinicopathological features(high T and N stage, positive tumor status, poor treatment effect and TP53 mutation). TNM stage has been used to assess the severity of tumor extent, lymph node invasion and distant metastasis since 1966 [ 49 ]. In our study, CHRDL1 is only related to T and N stage, not to M stage.…”
Section: Discussionmentioning
confidence: 99%
“…19 To be eligible for inclusion, patients should meet the following criteria: (1) pathologically confirmed NSCLC; (2) primary site codes from C34.0 to C34.9; (3) been of adult age; (4) been diagnosed between 2010 and 2016. In contrast, patients with the following conditions were excluded from the study: (1) diagnosed by either autopsy or death certificate; (2) had the second primary tumor; (3) lacked their follow-up status; (4) lacked details of clinicopathological information; (5) without BM or BM status missing/unknown. The flowchart of patient selection is shown in Figure 1.…”
Section: Patients Selectionmentioning
confidence: 99%
“…NSCLC is the most common lung cancer type, accounting for approximately 85% lung cancer cases. 5 , 6 NSCLC can be classified into three major subtypes: adenocarcinoma (40% of NSCLC), squamous (25–30% of NSCLC), and other subtypes. 7 , 8 It is estimated that >50% of NSCLC patients have already developed into (at least) stage III disease, which needs multimodality therapies.…”
Section: Introductionmentioning
confidence: 99%